2018
DOI: 10.1093/pm/pny055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Massage in Reducing the Pain and Anxiety of the Cardiac Surgery Critically Ill—a Randomized Controlled Trial

Abstract: Findings suggest that a 20-minute hand massage in addition to routine postoperative pain management can concomitantly reduce pain intensity, pain unpleasantness, and anxiety by two points on average on a 0-10 scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…Efficacy of individual modalities has been studied to an extent in randomized trials with specific patient populations. [7][8][9][10][11][12] A 2004 study observationally assessed the effectiveness of massage on pain in for IM delivered clinically in the inpatient setting, 30 and a 2016 protocol described an effectiveness study of acupuncture provided as part of routine inpatient care for pain and symptom management. 31 A strength of this study is the inclusion of patients across the hospital, and an individualized IM approach rather than specific modalities provides a valuable practice-based perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of individual modalities has been studied to an extent in randomized trials with specific patient populations. [7][8][9][10][11][12] A 2004 study observationally assessed the effectiveness of massage on pain in for IM delivered clinically in the inpatient setting, 30 and a 2016 protocol described an effectiveness study of acupuncture provided as part of routine inpatient care for pain and symptom management. 31 A strength of this study is the inclusion of patients across the hospital, and an individualized IM approach rather than specific modalities provides a valuable practice-based perspective.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although much research on integrative medicine (IM) modalities (e.g., massage, acupuncture, meditation) has been conducted in outpatient populations, 3 meta-analyses [4][5][6] and randomized controlled studies suggest that acupuncture, massage, and mind-body therapies, as provided adjunctively to conventional pain management, result in reduced pain for specific populations of inpatients, primarily postsurgical populations. [7][8][9][10][11][12] While assessment of efficacy via randomized trials provides valuable evidence for how well various IM modalities work in controlled settings, these studies do not capture the more variable contexts appropriate for clinical practice. Effectiveness research, that is, using observational study designs, is appropriate for practice-based research in realworld settings where interventions already have been implemented and/or are subjected to inherent variability and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that back massage can be effective in reducing anxiety components (physical, cognitive and behavioral). Similarly, the study by Boitor et al showed that massage is effective in reducing pain and anxiety in patients after [25]. In the study of Atashi et al and also in the study of Mohammadpour et al, the effect of Slow Stroke Back Massage (SSBM) on reducing anxiety in patients with stroke and patients undergoing cataract surgery has been mentioned [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…One of the massage techniques is Swedish massage A therapy, which was used to reduce anxiety [22]. The anxiolytic effects of massage have been confirmed in a variety of cases, including primiparous women, post-operative cardiac surgery patients, and patients with heart failure [24][25][26]. Since the effect of massage on reducing anxiety of mothers with preterm infants has not been investigated so far, this study aimed to investigate this issue.…”
Section: Introductionmentioning
confidence: 99%
“…3 Massage therapy, when done consistently, has been shown to reduce visual numeric pain scores by up to 2 points. [33][34][35] Massage is typically paired with decreasing sensory stimuli such as dimming lights and either muting alarms or decreasing the volume and providing earplugs or an eye mask to the patient. 3 This is often seen as a barrier to implementation of a massage protocol, given frequent disruptions in an ICU setting.…”
Section: Massage Therapymentioning
confidence: 99%